Resposta de forrageiras à adubação NPK no cerrado brasileiro: um estudo meta-analítico - Leite, Dagna Ariele da Costa (Universidade Federal do Tocantins, 2023)
Animal production in Brazil is mainly carried out in areas under pasture, most of which have some stage of degradation, especially in the Cerrado, due to inadequate animal management and lack of nutrient replacement. Therefore, this study aimed to analyze the response of forage grasses of the genus Brachiaria and Panicum to NPK fertilization in the Brazilian Cerrado through a meta-analytical study. Literature works from the last 30 years (1990 - 2020) were collected, defining specific criteria such as: (i) field study, (ii) under the Cerrado biome, (iii) with forages of the genus Panicum and Brachiaria, (iv) evaluating NPK fertilization versus a control with only N, P, K, NP, NK, PK or without NPK fertilization. According to the defined criteria, 19 works were collected, covering three regions, five states and the Federal District. In the studies, five forage species and seven different cultivars were used. The NPK fertilization increased forage productivity when compared to the control up to 4.5 times. The greatest response to NPK fertilization was obtained by forages of the genus Panicum in soils with sandy texture, very low phosphorus availability and organic matter content greater than 1%. Therefore, the management of pasture fertilization must take into account the genus of forage to be implemented, as well as the chemical properties of the soil.